The Influence of Brand Image and Product Innovation on Purchasing Decision of Kopi Kenangan at Tunjungan Plaza Surabaya - Gladys Adella Permatasari (NAROTAMA UNIVERSITY, Indonesia, 2021)
The development and growth of the culinary business is currently increasing in Indonesia, especially in Surabaya, especially coffee shops, this is marked by the rise of restaurants, cafes and coffee shops. Kopi Kenangan is one of the shops that popularized a typical Indonesian coffee milk drink which is popular with the name